Government’s Teaching Platform as an Intervening Influence of CEO-based leadership and Teacher Readiness Quality on the Successful Implementation of the Kurikulum Merdeka - Bhayangkara, Athalla Nauval; Supriyanto, Achmad; Imron, ali (Universitas Negeri Malang, 2023)
This research aims to analyze the influence of CEO-based leadership and teacher readiness quality through the independent teaching platform on the successful implementation of the kurikulum merdeka. This research was carried out at Pengmobil Middle Schools throughout Malang City, the sampling technique used was purposive random sampling, so that from a population of 300, 263 teachers and 11 school principals were obtained as research respondents. This research method is quantitative, with a structural model or SEM design using SmartPLS4 to examine the direct and indirect influence of exogenous variables on endogenous variables. The exogenous variables in this research are CEO-based leadership as X1, teacher readiness quality as X2, independent teaching platform as Z1 or intervening, and successful implementation of the kurikulum merdeka as Y1. Partial testing was carried out using a significance value of <0.05 in all tests. The test results show that Fcount > Ftable, which means there is a positive and significant influence. In detail, the analysis was carried out in 4 stages, namely (1) validity and reliability test, (2) model feasibility test which was represented in the chi square determination with a value of <3.00, SRMR with a value of <0.10, NFI with a score of >0.80 , d_g with a score of >0.05, and d_Uls with a score of >0.05, (3) bootstrapping will be allocated in assessing the significance of direct and indirect influence measurements which can be seen in the R2, F2, outer loading and cross loading values , and (4) blindfolding used to determine predictive associations. The results of this research showed that all hypotheses were accepted, both direct and indirect effects. Overall, exogenous variables contributed 81.3% of their influence on the successful implementation of the kurikulum merdeka, while the remaining 19.7% was influenced by other variables that had not been studied.